(untitled) (Geologica Macedonica, 2022)
For the study of hydrothermal alterations in the Borov Dol deposit, a total of 12 samples were taken, of which 10 samples from boreholes BD-335, BD-320 and BD-322, and 2 samples from the open pit mining Borov Dol. The material for the X-ray diffraction analyses was also prepared from the samples from which petrographic preparations were made. The following types of alterations have been determined from the conducted investigations: propylitization, chloritization, epidotization, argillitization, kaolinization, calcitization, silification, sericitization, bio-titization, adularization, and K-feldsparization. Some of the alterations are pre-ore or follow the formation of copper mineralization (silicification, sericitization and K-feldsparization), and some are post-ore (argillitization, calcitization, and kaolinization). The model of alterations follows the examples of porphyry systems, and the most significant alter-ations for the spatial distribution of copper mineralization in the Borov Dol deposit are sericitization, silicification, and K-metasomatism. Surface alterations are due mainly to limonitization and in places to argillite alteration. Propylitization gives the segment of the outer halo of alterations in this area.